2005
DOI: 10.1159/000083890
|View full text |Cite
|
Sign up to set email alerts
|

Tubular CD146 Expression in Nephropathies Is Related to Chronic Renal Failure

Abstract: Background: CD146, a member of the immunoglobulin superfamily, is mainly expressed at the endothelial junction. The soluble form of CD146 is increased in the serum of patients with chronic renal failure. The aim of the study was to investigate CD146 expression on biopsies of normal kidney and nephropathies. Methods: We did an immunohistochemical analysis of 10 normal renal tissues and 126 patients with nephropathies. Results: The mean age of the patients was 47.5 ± 18 years with 65% of men. At the time of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…31 The vascular ECs of the normal adult human kidney express CD146, but increases in vascular expression and de novo expression in tubular cells can occur in nephropathies. 32 Moreover, increased concentrations of soluble CD146 are observed in patients with chronic renal failure, correlating with EC injury markers. 33 A mouse model of renal ischemia/ reperfusion injury has revealed that cell therapy with human bone marrow-derived stem cells increases survival via regeneration of the peritubular vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…31 The vascular ECs of the normal adult human kidney express CD146, but increases in vascular expression and de novo expression in tubular cells can occur in nephropathies. 32 Moreover, increased concentrations of soluble CD146 are observed in patients with chronic renal failure, correlating with EC injury markers. 33 A mouse model of renal ischemia/ reperfusion injury has revealed that cell therapy with human bone marrow-derived stem cells increases survival via regeneration of the peritubular vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physiological angiogenesis, α6β1 integrin and MCAM interaction with α4-laminins may contribute to tissue regeneration as reported for nerves and liver . Notably, MCAM is expressed by mesenchymal stem cells and glomerular mesangial cells, and the latter cells use endogenous laminin-421 to migrate (Daniel et al, 2005;Berfield et al, 2006;Wang and Yan, 2013). The molecular interactions may also mediate leukocyte trans-endothelial migration during inflammation (Wondimu et al, 2004;Bardin et al, 2009;Flanagan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cell adhesion molecule (MCAM), also known as CD146, MUC18, MelCAM, A32 antigen, METCAM, and gicerin, is a cell-surface molecule of the Ig superfamily with expression in normal tissues restricted to vascular endothelial cells, smooth muscle cells, glomerular mesangial cells, Schwann cells, intermediate trophoblasts, mesenchymal stem cells, some leukocytes, and a few other cell types (Shih et al, 1998;Daniel et al, 2005;Wang and Yan, 2013). Originally identified as a tumor marker for melanoma (Lehmann et al, 1987), MCAM is also detected in prostate cancer, osteosarcoma, and other tumors, and its expression is closely related to tumor invasion and metastasis and poor survival .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of CD146 in physiological angiogenesis was illustrated by an earlier study of its regulation of intersegmental vessel development in zebrafish (9). During pathological angiogenesis, CD146 expression is upregulated in the endothelial cells involved in angiogenic diseases, including tumors (8), chronic renal failure (10), inflammatory bowel disease (11), and rheumatoid arthritis (12). The expression level of endothelial CD146 directly correlates with endothelial cell proliferation, migration, and tube formation (13,14).…”
mentioning
confidence: 99%